Analyzing the Effect of Causation in Covid-19 Business Interruption Insurance Claims: A Black-Letter Law Analysis of Causation within Business Interruption Insurance Cases - Naidoo, Jared (Department of Commercial Law, 2023)
The unprecedented Covid-19 lockdown response by governments around the world triggered a bevy of business interruption insurance claims. One of the key issues considered by the courts in adjudicating refuted claims was the question of causation. The question in its simplest form was this: did the virus or the government response cause the losses suffered by the insured? This paper analyzes the effect causation played in the adjudication of these business interruption insurance cases in South Africa, as well as the test case in the United Kingdom. Given the novelty of the issue, this paper narrows down on the causative link between the virus, the government response and the insurance claim, at the time of writing the paper, a topic not thoroughly focused on by other academics. This paper analyzes the case law to see how the courts dealt with the issue, but also proposes an alternative causation theory to consider and what the result of the courts' decision could have been had they followed that consideration. The main finding is that despite a reasonable alternative consideration of causations effect on the insurance claim, the courts' made the more appropriate decision, especially taking into account the overarching considerations of fairness. The result shows the major effect causation plays in business interruption insurance cases and the depth of the causative analysis goes much deeper than anticipated, however given the unanimous judgments from South Africa and the UK, the question of causation in Covid-19 business interruption claims seems to now be largely settled law.